COVID-19 Restrictions, Lifestyles, and Marital Conflicts: An Empirical Analysis of Marital Sustainability - Ozad, Bahire Efe; Jamo, Maryam Suleiman; Uygarer, Gulen (Mdpi, 2022)
Governments are taking precautions to limit the spread of the COVID-19 virus, including instituting social isolation policies that cover all aspects of life, such as closing public places such as worship centers, recreational facilities, work, schools, and shopping malls. The restrictions have a variety of sociological and psychological consequences on daily lifestyle of people, including marital conflict. Thus, this study investigates couples' lifestyles and conflicts during the COVID-19 pandemic lockdown in Nigeria based on the frustration-aggression hypothesis. The study used a sample of 373 adults obtained from a combined offline and online cross-sectional survey that was conducted via face-to-face contact, email questionnaire, and Google form (distributed via social media groups and emails). We used descriptive statistics to analyze the data. The findings reveal that the COVID-19 pandemic restrictions (lockdown) led to reduced or lost income, financial uncertainty, job insecurity, and social isolation. Consequently, the COVID-19-pandemic exacerbated poverty and insecurity, as well as insufficient judicial processes. These resulted in misery and violence against spouses, which aggravated marital strife in the country.
Keywords: COVID-19; lockdown; lifestyle; couple conflict; Nigeria